Integrative approach in management of recurrent pilonidal sinus in a rare case of polycythemia vera - Komal Dhalani; Tukaram Dudhamal; Yogesh Meghani (BLDE University Journal of Health Sciences)
Pilonidal sinus is a common surgical disease that affects young hairy adults involving characteristically the sacrococcygeal area. The best surgical method is being searched for the treatment of pilonidal sinus in terms of minimizing recurrence. A 35-year-old male patient consulted the outpatient department with complaints of pain and pus discharge from a previously operated scar at the natal cleft along with difficulty in sitting. The patient reported a history of recurrent pilonidal sinus for which he was operated on twice in 2020 and 2021, so the case was diagnosed as a recurrent case of pilonidal sinus. Preoperative blood investigations revealed that the patient had polycythemia vera with idiopathic etiology. The patient was advised for phlebotomy and then excision of the tract of the pilonidal sinus was done under local anesthesia. After excision, the wound was kept open for healing by secondary intention. Along with that, two sittings of Jaloka Avacharan were done during treatment to improve healing. Daily dressing with Haridra powder was done. The wound was completely healed within 40 days. After complete healing, the patient was advised for laser epilation. No recurrence was observed up to 2 years after complete healing, and the patient is advised further follow-up to check recurrence.